Caucasus in Context: M.Yu. Lermontov’s Reflections on Man and Fate of History - I. A. Kiseleva; K. A. Potashova (Научный диалог, 2023)
The article examines the specificity of Lermontov’s vision and depiction of the Caucasus world. It reconstructs Lermontov's philosophy of history in the context of the Caucasian War. The study reveals the cultural and historical conditioning of the poet’s imagery and ideas, and the dominant values of the Caucasian world in his artistic heritage. The article focuses on how Lermontov portrays the everyday existence of the highlanders, whose images he sees as representing the natural man in both his attractiveness and his corrupt passions. By depicting the Caucasus world in its natural and cultural uniqueness, Lermontov highlights elements of the highlander's mentality that are close to his own, and notes the convergence of Russian and Caucasian cultures. Reproducing the cultural traditions of the peoples of the North Caucasus, the poet reflects on the interaction between their clan relationships, individualistic elements, and Islamic cultural traditions. The hypothesis of the study is related to the dynamics of Lermontov’s depiction of the significance of Islam in the life of the peoples of the North Caucasus. In his early Caucasian poems, Islam appears as an external attribute of highlander life that has little impact on their consciousness, merging with their clan tradition. In his later works, however, Lermontov begins to understand Islam in its cultural and political function, which, when combined with highlander independence, can contribute to productive state interaction between Russians and the indigenous peoples of the Caucasus.